INFORMATION RETRIEVAL AND DATA MINING: CASE STUDY: COVID-19 DASHBOARD ANALYSIS (Environmental Smoke, 2021)
Research data mining requires the use of information systems and complex methods of searching, accessing, retrieving, and appropriating information on the web of data. Platforms such as Google Scholar Google, Elsevier, JSTOR, ResearchGate, ScienceDirect and the ones provided by commonly used universities identified with search terms. The challenge is to ensure that researchers are being exposed to the state-of-the-art networked knowledge production. This study aims to analyze the process of searching and retrieving information, reflect on the role of information systems in the search result and the informational skills of the researcher in view of the quality of information retrieved. Case Study: COVID-19 Dashboard Analysis.